PENGARUH PEMBERIAN SALIVA MANUSIA TERHADAP PROLIFERASI FIBROBLAS KULIT NORMAL (SEBUAH MODEL FASE PROLIFERASI PENYEMBUHAN LUKA) - , LUTIA UTAMI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Wound healing is a dynamic process that involves four phases. Growth factor (GF) is one of factors that play a role in wound healing. Treatment with rich growth factor substance like platelet rich plasma (PRP) and platelet rich fibrin (PRF) are costly and need a complicated procedure. The aim of this study is to determine whether human saliva can increase the proliferation of human skin fibroblast. Cultured normal human skin fibroblasts 6th passage divided into 10 groups, the control group and the group treated with 1 hour, 2 hour, and 6 hour fasting saliva, each of which consists of a concentration of 25%, 50%, and 100%. Fibroblast proliferation was measured with spectrophotometer by using MTT assay. Comparison of mean proliferation of fibroblasts were analyzed with Friedman test and post hoc by Wilcoxon test. The mean proliferation of fibroblasts increased significantly (p<0.05) in the group given 1 hour fasting saliva in concentrations of 25% and 50% compared to the control group, but the administration of 1 hour fasting saliva 50% concentration showed a significant decrease in mean fibroblast proliferation compared to the administration of 1 hour fasting saliva of 25% concentration. Giving 2 hour fasting saliva of 25% showed a significant increase in mean fibroblast proliferation (p<0.05) when compared to controls. There is an increase in the mean proliferation of fibroblasts in the administration of 6 hour fasting salivary concentrations of 25% and 50% compared to the control group, but it was not significant (p>0.05). Administration of 1 hour, 2 hour and 6 hour fasting saliva of 100% concentration showed that the reduction in mean fibroblast proliferation was significant (p<0.05) compared to the control group. As a conclusion, human saliva can increase the proliferation of normal skin fibroblast in vitro.